METHODIC APPROACH TO THE EVALUATION OF SUSTAINABLE AND SAFE SOCIAL AND ECONOMIC DEVELOPMENT OF THE TERRITORIES - Krivorotov, Vadim; Kalina, Alexei (Вісник Економіки, 2017)
Major problems of social and economic development of the country under the conditions of the world financial crisis are described in the article. Methodological basics of the research of sustainable and safe social and economic development (SSSED) of the territories of different levels are suggested in the article. Major components in the scheme of research of SSSED are characterized. A methodological approach to differentiate SSSED of the territories of the regional level is analyzed in the article. Algorithms evaluating the state of the economy from the view-point of SSSED provision and from the view-point of the indicators of sustainability of the direction of social and economic development are provided in the article.